2019
DOI: 10.7454/msk.v23i3.1171
|View full text |Cite
|
Sign up to set email alerts
|

Chronic constipation among community-dwelling older people in the East Coast region of Peninsular Malaysia

Abstract: Background:This study aimed to investigate the prevalence, symptoms, and factors associated with chronic constipation among community-dwelling older people in the East Coast region of Peninsular Malaysia. Methods: A cross-sectional study was conducted in four selected health clinics using stratified cluster sampling. A face-to-face interview was carried out among the elderly outpatients, in order to complete a structured questionnaire. Results: A total of 400 participants were included in the study. The mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The prevalence of this phenomenon can vary depending on geographical regions, ranging from 0.7%-29.6% in children, and from 2.0%-35.0% among adults in Europe, Oceania, and North America (Mugie, Benninga & Di Lorenzo, 2011). In developing countries like Malaysia and Indonesia, the prevalence of constipation is quite high at 32.3% and 58.0%, respectively (Wahab et al, 2019;Yudiyanto, 2018). It was reported that constipation afflicted a wide age range, starting at age 60 years (Wahab et al, 2019) or even earlier (12-17 years old) (Yudiyanto, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of this phenomenon can vary depending on geographical regions, ranging from 0.7%-29.6% in children, and from 2.0%-35.0% among adults in Europe, Oceania, and North America (Mugie, Benninga & Di Lorenzo, 2011). In developing countries like Malaysia and Indonesia, the prevalence of constipation is quite high at 32.3% and 58.0%, respectively (Wahab et al, 2019;Yudiyanto, 2018). It was reported that constipation afflicted a wide age range, starting at age 60 years (Wahab et al, 2019) or even earlier (12-17 years old) (Yudiyanto, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries like Malaysia and Indonesia, the prevalence of constipation is quite high at 32.3% and 58.0%, respectively (Wahab et al, 2019;Yudiyanto, 2018). It was reported that constipation afflicted a wide age range, starting at age 60 years (Wahab et al, 2019) or even earlier (12-17 years old) (Yudiyanto, 2018).…”
Section: Introductionmentioning
confidence: 99%